Ethyl 4-[(3,5-di-tert-butyl-2-hydroxybenzyl)amino]benzoate - Shakir, R.M.; Ariffin, A.; Ng, S.W. (International Union of Crystallography, 2010)
The title amine, C24H33NO3, has two substituted aromatic rings at either end of the -CH2NH- linkage [C-aryl-CH2-NH-C-aryl torsion angle = 77.4 (3)degrees]. The amino and hydroxy groups are hydrogen-bond donors to the carbonyl O atom of an adjacent molecule. These hydrogen bonds give rise to a chain that runs along the b axis. One of the tert-butyl groups is disordered over two positions with a site-occupation factor of 0.834 (6) for the major occupied site.